E-039 Endovascular flow-diverting stents for intracranial aneurysms. (22nd July 2019) - Nada, A; Brunet, M; Chen, S; Sur, S; Elwardany, O; Zenonos, G; Jahmshidi, A; MccCarthy, D; Sheinberg, D; Zaher, A; Elsherbiny, M; Kassem, M; et al.
Abstract : Background and purpose: Flow-diverting devices now offer a treatment alternative for cerebral aneurysms. The concept of these devices is to promote thrombosis of aneurysms without filling the aneurysm cavity by deviating the blood flow away from the aneurysm neck which means treatment of the diseased segment harboring the aneurysm instead of treating the aneurysm itself. We present the results of a large single-center series of patients treated with the PED, including long-term follow-up. Materials and methods: Between January 2015 and February 2019, sidewall aneurysms with a neck (≥2 mm to 19 mm) or unfavorable dome-neck ratio (≤1.5); large/giant, fusiform, M1 dysplastic aneurysms, dissecting, blister like, and recurrent sidewall aneurysms; aneurysms at difficult angles; and aneurysms in which a branch was originating directly from the sac were treated with the PED. Patients were pre-medicated with dual antiplatelet medications. Data, including demographics, aneurysm features, clinical presentation, complications, results, and follow-up information are presented. Results: One hundred and fourteen aneurysms in 114 patients were treated. Of these, (100%) PEDs were used for treatment. Adjunctive coiling was performed in 73 aneurysms (64%). Symptomatic in-construct stenosis was detected in 1 patient (0.9%) treated with percutaneous trans-arterial angioplasty. Any event rate as (Contrast extravasation and ICH, M1 occlusion or perforation, ICA occlusion, brain stem stroke, new SAH at the same side of treatment, ASDH, 3rd nerve palsy, Femoral pseudo aneurysm, breaking of delivery wire, snare of microwire, worsening of the double vision) was 9/114 (7.8%), with a permanent morbidity of 4.3% and mortality of 0.9%. Control angiography was available in 108 (94.7%) patients. The aneurysm occlusion rate was 91.2% in 6 months, increasing to 94.6% in one year. Conclusions: Flow diverters allow for the endoluminal reconstruction of a parent artery for the treatment of complex and difficult-to-treat aneurysms. There are multiple devices on the market, but the PED is the most-studied and the only device with FDA approval. Published aneurysm occlusion rates are favorable with an acceptable adverse event rate when used for approved indications. Disclosures: A. Nada: None. M. Brunet: None. S. Chen: None. S. Sur: None. O. Elwardany: None. G. Zenonos: None. A. Jahmshidi: None. D. MccCarthy: None. D. Sheinberg: None. A. Zaher: None. M. Elsherbiny: None. M. Kassem: None. S. Serag Eldin: None. N. Mansour Ali: None. A. Abd Elmoneim Ezz Eldin: None. J. Thomson: None. D. Yavagal: None. E. Peterson: None. R. Starke: None.